Orodja za krmiljenje delovnih procesov - Kovačič, Andrej (Uporabna informatika (Ljubljana), 1997)
In the following article the author presents the opportunities and conditions for the successful implementation of modern tools for workflow management. Special attention is drawn to the business process of an organization as well as to the problems of its renovation and informatization. Author defines the methods, tools and selection criteria for tools in the field of workflow management.
Keywords: delovni procesi; krmiljenje; poslovanje podjetja